2022
DOI: 10.1155/2022/2805004
|View full text |Cite
|
Sign up to set email alerts
|

Organic Amendments: Direct Application and Residual Effects on Vegetative and Reproductive Growth of Hot Pepper

Abstract: The high production potential of coffee and animals in the Gedeo zone that could produce huge amounts of coffee pulp and animal manure wastes has been polluting the environment. In this sense, this study was aimed at averting pollution and managing plant and animal wastes, focusing on the effect of coffee pulp and animal manure in the form of vermicompost, biochar, and ordinary compost on hot pepper vegetative and reproductive growth. A 15 ton per hectare of each treatment was applied in a randomized complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 66 publications
(77 reference statements)
3
5
0
Order By: Relevance
“…Hazrat et al [ 37 ] also revealed that the highest application rate of vermicompost even produced the maximum number of fruits of chilli. This finding was also in agreement with the finding of Berhe et al [ 21 ] who mentioned that maximum fruit numbers were recorded from the plant supplied with the maximum application rate of CEV followed by the highest application of CEV_CDV.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Hazrat et al [ 37 ] also revealed that the highest application rate of vermicompost even produced the maximum number of fruits of chilli. This finding was also in agreement with the finding of Berhe et al [ 21 ] who mentioned that maximum fruit numbers were recorded from the plant supplied with the maximum application rate of CEV followed by the highest application of CEV_CDV.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, Olowoake et al [ 14 ] revealed that the application rate of vermicompost positively affects fruit length of Cucumber crop. This result was also supported by the findings of Berhe et al [ 21 ] who reported that longer fruit length was recorded from the direct application of 15 t/ha Eisenia fetida vermicompost followed by 15 t/ha combination of Eisenia fetida and Dendrobaena veneta vermicompost, which might be due to the ability of the worms to produce hormones for crop growth so as to increase the fruit length of pepper.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations